Decoction, infusion and hydroalcoholic extract of Origanum vulgare L.: different performances regarding bioactivity and phenolic compounds - Martins, Natália (2014)
Bioactivity of oregano methanolic extracts and essential oils is well known. Nonetheless, reports using aqueous extracts are scarce, mainly decoction or infusion preparations used for therapeutic applications. Herein, the antioxidant and antibacterial activities, and phenolic compounds of the infusion, decoction and hydroalcoholic extract of oregano were evaluated and compared. The antioxidant activity is related with phenolic compounds, mostly flavonoids, since decoction presented the highest concentration of flavonoids and total phenolic compounds, followed by infusion and hydroalcoholic extract. The samples were effective against gram-negative and gram-positive bacteria. It is important to address that the hydroalcoholic extract showed the highest efficacy against Escherichia coli. This study demonstrates that the decoction could be used for antioxidant purposes, while the hydroalcoholic extract could be incorporated in formulations for antimicrobial features. Moreover, the use of infusion/decoction can avoid the toxic effects showed by oregano essential oil, widely reported for its antioxidant and antimicrobial properties.